Coronary Subclavian Steal Syndrome and Acute Anterior Myocardial Infarction: A New Treatment Dilemma in the Era of Primary Percutaneous Coronary Intervention. Issue 1 (7th July 2015) - Iglesias, Juan F.; Degrauwe, Sophie; Monney, Pierre; Glauser, Frédéric; Qanadli, Salah D.; Eeckhout, Eric; Muller, Olivier
Abstract : Supplemental Digital Content is available in the text.